Sitz Im Leben dalam 1 Timotius 2:11-12: Latar Belakang Instruksi kepada Wanita untuk tidak Mengajar dan Memerintah Pria - Stella, Yunita (Pusat Studi Pentakosta Indonesia, 2023)
The debate regarding the text of 1 Timothy 2:11-12 concerning the role of women in teaching and leadership within the church has become an exceedingly controversial issue. Some have employed this text as a tool to marginalize and oppress women in the church. The purpose of this research is to uncover the Sitz Im Leben that underlies the writing of 1 Timothy 2:11-12 in relation to the instructions given to women not to teach and have authority over men. The method employed is historical analysis, involving the study of the background of the book and its content related to the passage, encompassing various considerations including the meanings of people, places, and events. The results of this research indicate that the presence of the Artemis cult and the